2017
DOI: 10.1371/journal.pone.0179886
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic diversity of camu-camu [Myrciaria dubia (Kunth) McVaugh] in the Peruvian Amazon

Abstract: Camu-camu [Myrciaria dubia (Kunth) McVaugh] is currently an important and promising fruit species grown in the Peruvian Amazon, as well as in Brazil, Colombia, and Bolivia. The species is valued for its high content of fruit-based vitamin C. Large plantations have been established only in the last two decades, and a substantial part of the production is still obtained by collecting fruits from the wild. Domestication of the species is at an early stage; most farmers cultivate the plants without any breeding, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…However, 85 % of this camu-camu comes from uncultivated areas, i.e., it is collected from natural stands in the floodplains of the upper Amazon River and its tributaries (IZQUIERDO GÓMEZ;TONG GATTY, 2018). Paradoxically, little is known about the state of the morphological variability of camu-camu that grows in uncultivated areas (MARTIN et al, 2014;ŠMÍD et al, 2017). Hence, information about camu-camu in these uncultivated localities, as well as evaluation of the quality of materials in nearby cultivated areas, can contribute to the process of domestication and improvement of the species, as well as to the conservation and management of uncultivated populations and the ecosystems of which they are part (ŠMÍD et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 85 % of this camu-camu comes from uncultivated areas, i.e., it is collected from natural stands in the floodplains of the upper Amazon River and its tributaries (IZQUIERDO GÓMEZ;TONG GATTY, 2018). Paradoxically, little is known about the state of the morphological variability of camu-camu that grows in uncultivated areas (MARTIN et al, 2014;ŠMÍD et al, 2017). Hence, information about camu-camu in these uncultivated localities, as well as evaluation of the quality of materials in nearby cultivated areas, can contribute to the process of domestication and improvement of the species, as well as to the conservation and management of uncultivated populations and the ecosystems of which they are part (ŠMÍD et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite years of research, camu-camu is still in the process of domestication (PINEDO-PANDURO et al, 2004). Therefore, uncultivated plants, as well as cultivated plants, still show great phenotypic variability in their various morphological, physiological and agronomic characteristics (PINEDO-PANDURO et al, 2004;ŠMÍD et al, 2017). Since the cultivated populations of camucamu have not yet been highly selected for morphological characteristics of the fruits, there is still potential to select plants with larger fruits from uncultivated populations (ŠMÍD et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Genome size (~230 Mb) is the smallest known (unpublished data) of the Myrtaceae family, which range between 234 Mb for Myrciaria glazioviana [6] and 2080 Mb for Syzygium cumini [36]. Genetic diversity studies [37][38][39][40][41], conducted with expressed sequence tags (ESTs) and simple sequence repeats (SSRs or microsatellites) of samples collected from wild populations, germplasm collections, and crop populations from Brazil and Peru, found that the average expected heterozygosity is larger than the average observed heterozygosity (0.67 vs. 0.41). Likewise, the populations exhibited great genetic differentiation measures (F ST = 0.26) in agreement with Hartl and Clark classification [42].…”
Section: Karyotype Genome Size and Genetic Diversitymentioning
confidence: 99%
“…At that time, the presence of genetic structure was demonstrated among populations (two genetic groups) with an average heterozygosity of 0.08-0.14. Subsequent studies have analyzed the genetic diversity in germplasm collections and cultured populations using DNA markers, such as rapid amplification of polymorphic DNA (RAPD) [45], inter simple sequence repeat (ISSR) [8], expressed sequences tag-simple sequence repeats (EST-SSR) [9,46,47], and SSR [10,11], also known as microsatellite markers. Overall, these investigations found that the average expected heterozygosity (He = 0.67 AE 0.19, range of 0.45-0.88) was greater than the average observed heterozygosity Likewise, the average intrapopulation genetic diversity (average 74.89%, range of 65-79%) is $3 times greater than average interpopulation genetic diversity (average 25.10%, range of 20-35%).…”
Section: Genetic Diversitymentioning
confidence: 99%
“…This plant species possesses a diploid genome, and their genome size (230 Mb) is in the range of other Myrtaceae species [3][4][5][6]. Populations exhibit moderate genetic diversity and genetic structuring [7][8][9][10][11]. Camu camu produces several essential nutrients such as amino acids, polyunsaturated fatty acids, B-complex vitamins, and high quantities of vitamin C [2,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%